Self-Evaluations and Performance: Evidence from Adolescence - Oliver Himmler; Tobias Koenig (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2012)
A positive view of the self is often portrayed as a valuable asset in the sense that it can have performance enhancing properties. Using data on self-esteem - the most fundamental manifestation of positive self evaluations - and high school grade point averages of American students we produce results in line with this idea and find a positive link between favorable self-evaluations and higher levels of educational performance. However, when we exploit exogenous variation in self-esteem due to adolescent skin problems in order to account for the possible endogeneity of self-esteem, this finding is reversed and we obtain a negative effect on performance. We discuss mechanisms that may generate such an adverse causal effect of positive self-evaluations, and conclude that self-esteem and effort need not always be complements but can actually be substitutes.
Keywords: I2; J24; 330; Self-evaluations; Self-esteem; Non-cognitive Skills; Human Capital; Performance